Marshall cavendish cambridge primary maths activity book 1 - Soh, Christina; Soon, Spario (Marshall Cavendish Education Singapore, 2017)
The "Maths 1, Activity Book" provides interactive exercises and fun activities that reinforce the concepts taught in the Pupil's Book. It includes games, puzzles, and hands-on tasks to promote engagement and practical application of math skills, making learning enjoyable.